ANALYSIS OF PT TELKOM INDONESIA (PERSERO) TBK'S READINESS FOR CORPORATE TRANSFORMATION FROM A BUSINESS-TO-CONSUMER (B2C) MODEL TO A DIGITAL BUSINESS-TO-BUSINESS (B2B) MODEL IN RESPONDING TO GLOBAL BUSINESS COMPETITION: A CASE STUDY OF PT TELKOM INDONESIA (PERSERO) TBK - Mikael Julian Irsa; Mahir Pradana; Yogi Suprayogi (PT. Jurnal Center Indonesia Publisher, 2026)
The Indonesian telecommunication industry is currently experiencing saturation in the Business-to-Consumer (B2C) market segment, prompting PT Telkom Indonesia (Persero) Tbk to aggressively execute business transformation by shifting toward a Business-to-Business (B2B) Digital model to maintain relevance amidst increasingly competitive and dynamic global business competition. This shifting phenomenon demands comprehensive internal readiness, particularly regarding resource orchestration and marketing ambidexterity maturity to balance traditional connectivity business with the exploration of high-value digital service innovation. This research employs a quantitative methodology with descriptive and causal approaches to dissect and objectively measure the level of organizational readiness in facing such market disruptions. Primary data collection was conducted with 385 respondents consisting of employees and strategic stakeholders involved in the transformation process at PT Telkom Indonesia using a nonprobability sampling technique with a purposive sampling method. All collected data were subsequently processed and tested using the SmartPLS version 4 analysis tool to ensure accuracy in modeling the complex relationships between the variables. The data analysis techniques utilized include descriptive statistics to provide a general overview of the data and variance-based Structural Equation Modeling (PLS-SEM) to test the significance of relationships between latent variables within the research model. The research findings project that corporate strategy significantly and positively influences business transformation success and B2B Digital model development, while simultaneously providing a strong direct impact on strengthening the company's competitiveness at the global level. The analysis results also indicate that internal transformation effectiveness and the implementation of B2B digital solutions are primary determinants capable of substantially enhancing the company's ability to compete across borders in the digital platform era. Furthermore, the mediating roles of business transformation and B2B Digital model variables have proven to be crucial in reinforcing the link between corporate strategic orientation and the achievement of sustainable international competitive advantage. Overall, this study provides an empirical foundation regarding the importance of precise resource orchestration for Telkom Indonesia to realize its vision as a preferred digital telco capable of winning competition in international markets.